Toward digital participation in individuals with Autism Spectrum Disorder - Pliska, Larissa; Neitzel, Isabel; Ritterfeld, Ute (Frontiers in Communication, 2023)
Digital participation might have great potential for the everyday lives of individuals with Autism Spectrum Disorder (ASD). Previous research suggests that children with ASD enjoy and favor usage of digital technologies. As informative research on this topic is still sparse, this paper makes a contribution towards a better understanding of media usage in children with ASD. Parents of 15 boys aged 6 to 11 diagnosed with ASD in Germany were asked about their children's media usage. For comparison, parents of 78 typically developing (TD) children were surveyed online. Statistical analyses reveal no differences between boys with and without ASD in media use, frequency, and reasons for use. However, there is a significant group difference in parents' perceptions of difficulty of restricting their child's media use: Parents of children with ASD reported greater difficulties of restriction of their child's media use than parents of TD children. Digital media is an integral part of the daily lives of children with ASD and has the potential to increase the social inclusion of people with ASD through digital participation.